Medical officers’ awareness, involvement and training in dysphagia management - Yong, Deborah Xinyi; Affizal Ahmad,; Malarvini Vesualingam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Awareness, involvement and training in dysphagia management are essential to ensure that patients are appropriately assessed for dysphagia and provided with intervention. The study aimed to identify levels of awareness, involvement and training of medical officers in dysphagia management. A total of 51 medical officers from the family medicine, medical, otorhinolaryngology, surgery, and neurosurgery departments in Hospital Universiti Sains Malaysia participated in the study. Levels of awareness, involvement and training of medical officers in dysphagia management were reported using descriptive analysis. Results indicate that medical officers lacked awareness and training in dysphagia management. Referral rates to speech-language pathologists for dysphagia management were low with 58.4% of medical officers having had seldom or never referred patients. The results provide valuable information for addressing dysphagia management in the hospital.